2021
DOI: 10.4081/jphr.2021.2273
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Health Belief Model to Assess U.S. College Students’ Perceptions of Covid-19 and Adherence to Preventive Measures

Abstract: Background: This study utilized the Health Belief Model to examine college students’ perceptions of the COVID-19 pandemic. It examined the extent to which the Health Belief Model and perceived threat are associated with the adoption of COVID-19 preventive measures among college students.Design and Methods: An online questionnaire was utilized and sent to a simple random sample of college students at a large Midwestern university in the United States between May and July of 2020. The number of undergraduate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The present study examined the constructs collectively as indicators of underlying perceptions of COVID-19 threat, healthcare discrimination, and U.S. healthcare system inequities and found that distinct classes of these perceptions were associated with students' mental and physical health. In the COVID-19 context, much of the existing literature on college students' health-related perceptions examined the influence of perceived COVID-19 threat on preventive behaviors (39), therefore, this study extends prior research by focusing on the association between these health-related perceptions and self-rated mental and physical health. This extension has wide-reaching implications given that self-rated health is a rich, complex construct previously associated with biomarkers of stress, chronic disease, and mortality (40).…”
Section: Discussionmentioning
confidence: 79%
“…The present study examined the constructs collectively as indicators of underlying perceptions of COVID-19 threat, healthcare discrimination, and U.S. healthcare system inequities and found that distinct classes of these perceptions were associated with students' mental and physical health. In the COVID-19 context, much of the existing literature on college students' health-related perceptions examined the influence of perceived COVID-19 threat on preventive behaviors (39), therefore, this study extends prior research by focusing on the association between these health-related perceptions and self-rated mental and physical health. This extension has wide-reaching implications given that self-rated health is a rich, complex construct previously associated with biomarkers of stress, chronic disease, and mortality (40).…”
Section: Discussionmentioning
confidence: 79%
“…The percentage was even lower among medical students, at 23%. As future healthcare workers, university students in health schools should be aware that they can provide cues to action through providing public health recommendations [ 68 ]. Lack of disease knowledge can negatively influence the recommendations of vaccine acceptance and adherence to public health intervention measures.…”
Section: Discussionmentioning
confidence: 99%
“…Based on TPB the immediate predictors of the behavior are behavioral intention with constructs of attitude, subjective norm, and perceived behavioral control. 5 The TPB constructs (attitude, subjective norm, and perceived behavioral control) and behavioral intention were positively associated with hand washing practice, 19 , 63 , 64 social distance, 65 67 face mask-wearing, 64 , 68 71 social isolation, 72 , 73 and enhanced community quarantine. 74 This finding suggested that the TPB could be used to predict health preventive behavior; therefore, it is important to guide the development of effective healthy messages on COVID-19 preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%